Assessing the impact of annual health screenings in identifying noncommunicable disease risk factors within Qatar’s primary health care corporation Qatari registered population - Al-Abdulla, Samya Ahmad; Haj Bakri, Ahmad; Mansaray, Mariama Aminata; Al-Kuwari, Mohamed Ghaith (Frontiers in Public Health, 2024)
Background Noncommunicable diseases (NCDs) are a significant global health burden, including in Qatar, where cardiovascular diseases cause mortality. This study examines the outcomes of the annual health checkup implemented by the Primary Health Care Corporation (PHCC) in Qatar in detecting NCDs risk factors among Qataris aged 18+ years. Methods A cross-sectional study design was implemented to calculate the prevalence of behavioural and metabolic NCDs risk factors among Qataris who underwent annual health checkups between 2017 and 2019. Data on age, gender, tobacco consumption, height, weight, blood pressure, glycated haemoglobin (HbA1c), and cholesterol levels were extracted from electronic medical records. Results In 2019, Qatar experienced an 80% rise in Annual Health checkups attendance compared to 2017. Tobacco use fluctuated between 11.79 and 12.91%, peaking at 35.67% among males in 2018. Qataris with elevated blood pressure dropped from 29.44% in 2017 to 18.52% in 2019. Obesity decreased from 48.32 to 42.29%, more prevalent in females. High HbA1c levels reduced from 13.33 to 8.52%, while pre-diabetic levels rose from 21.1 to 25.52%. High cholesterol ranged from 7.31 to 9.47%. In a regression analysis, males had 2.28 times higher odds of elevated blood pressure and 1.54 times higher odds of high HbA1c, with a 0.68 lower odds of obesity compared to females. Ages 36 and above had 2.61 times higher odds of high cholesterol compared to younger age groups. Conclusion The annual health screening has shown promising results in detecting and addressing NCDs risk factors among Qataris. The attendance rate has increased over the three-year period, and there has been a decrease in the prevalence of elevated blood pressure, obesity, and high HbA1c levels. However, tobacco consumption and pre-diabetic levels remain significant concerns. These findings can guide the implementation of tailored preventative and curative services to improve the health and well-being of the Qatari population.